INTERNET SELF-EFFICACY AND INTERACTION OF STUDENTS IN MATHEMATICS COURSES - Asahid, Remelyn L (MATTER: International Journal of Science and Technology, 2018)
Interaction creates an essential environment in learning Mathematics effectively and opportunities for teachers and students to talk about their own thinking, and reflection on students’ learning process. Since interaction in the classroom can reveal students’ views and ideas, it would be important to study the underlying relationship between internet self-efficacy and interaction in Mathematics courses. The study used descriptive-correlational technique involving 439 students from the selected universities and colleges in Davao City, and criterion sampling was used. Findings revealed that the respondents had extensive internet self-efficacy and interaction in Mathematics courses. The results further revealed a strong significant relationship between internet self-efficacy and interaction in Mathematics courses. The results of regression analysis also revealed that the three predictors of internet self-efficacy had significant influence on interaction in Mathematics courses and suggested that a reasonable percentage of the variance on interaction in Mathematics courses can be explained by the three predictors. Furthermore, among the three predictors, extent of self-efficacy in system manipulation was the most influential factor that contributed to the level of interaction in Mathematics courses. Lastly, future research should include more variables that could somehow affect the level of interaction in Mathematics courses.